Decrease of the spatial variability and local dimension of the Euro-Atlantic eddy-driven jet stream with global warming - Robin Noyelle; Vivien Guette; Akim Viennet; Bénédicte Colnet; Davide Faranda; Andreia N. S. Hisi; Pascal Yiou (Climate Dynamics, 2024)

Investigating the typicality of the dynamics leading to extreme temperatures in the IPSL-CM6A-LR model - Robin Noyelle; Pascal Yiou; Davide Faranda (Climate Dynamics, 2024)

Correcting biases in tropical cyclone intensities in low-resolution datasets using dynamical systems metrics - Davide Faranda; Gabriele Messori; Stella Bourdin; Mathieu Vrac; Soulivanh Thao; Jacopo Riboldi; Sébastien Fromang; Pascal Yiou (Climate Dynamics, 2023)

A methodology for attributing severe extratropical cyclones to climate change based on reanalysis data: the case study of storm Alex 2020 - Mireia Ginesta; Pascal Yiou; Gabriele Messori; Davide Faranda (Climate Dynamics, 2023)

Correction to: Cold waves still matter: characteristics and associated climatic signals in Europe - Benjamin Quesada; Robert Vautard; Pascal Yiou (Climatic Change, 2023)

Cold waves still matter: characteristics and associated climatic signals in Europe - Benjamin Quesada; Robert Vautard; Pascal Yiou (Climatic Change, 2023)

Changes in temperature–precipitation correlations over Europe: are climate models reliable? - Mathieu Vrac; Soulivanh Thao; Pascal Yiou (Climate Dynamics, 2023)
Inter-variable correlations (e.g., between daily temperature and precipitation) are key statistical properties to characterise probabilities of simultaneous climate events and compound events. Their correct simulations from climate models, both in values and in changes over time, is then a prerequisite to investigate their future changes and associated impacts. Therefore, this study first evaluates the capabilities of one 11-single run multi-model ensemble (CMIP6) and one 40-member single model initial-condition large ensemble (CESM) over Europe to reproduce the characteristics of a reanalysis dataset (ERA5) in terms of temperature–precipitation correlations and their historical changes. Next, the ensembles’ correlations for the end of the 21st century are compared. Over the historical period, both CMIP6 and CESM ensembles have season-dependent and spatially structured biases. Moreover, the inter-variable correlations from both ensembles mostly appear stationary. Thus, although reanalysis displays significant correlation changes, none of the ensembles can reproduce them, with internal variability representing only 30% on the inter-model variability. However, future correlations show significant changes over large spatial patterns. Yet, those patterns are rather different for CMIP6 and CESM, reflecting a large uncertainty in changes. In addition, for historical and future projections, an analysis conditional on atmospheric circulation regimes is performed. The conditional correlations given the regimes are found to be the main contributor to the biases in correlation over the historical period, and to the past and future changes of correlation. These results highlight the importance of the large-scale circulation regimes and the need to understand their physical relationships with local-scale phenomena associated to specific inter-variable correlations.

Seasonal circulation regimes in the North Atlantic: Towards a new seasonality - Florentin Breton; Mathieu Vrac; Pascal Yiou; Pradeebane Vaittinada Ayar; Aglaé Jézéquel (International Journal of Climatology, 2022)
European climate variability is shaped by atmospheric dynamics over the North Atlantic and local processes. Better understanding their future seasonality is essential to anticipate changes in weather conditions for human and natural systems. We explore atmospheric seasonality over 1979–2017 and 1979–2100 with seasonal circulation regimes (SCRs), by clustering year‐round daily fields of Z500 from the ERA‐Interim reanalysis and 12 Coupled Model Intercomparison Project phase 5 (CMIP5) climate models (historical and RCP8.5 runs). The spatial and temporal variability of SCR structures and associated patterns of surface air temperature are investigated. Climate models have biases but reproduce structures and evolutions of SCRs similar to the reanalysis over 1979–2017: decreasing frequency of winter conditions (starting later and ending earlier in the year) and the opposite for summer conditions. These changes are stronger over 1979–2100 than over 1979–2017, associated with a large increase of North Atlantic seasonal mean Z500 and temperature. When using more SCRs (more freedom in definition of seasonality), the changes over 1979–2100 correspond to a long‐term swap between SCRs, resulting in similar structures (annual cycle and spatial patterns) relative to the evolution of seasonal mean Z500 and temperature. To understand whether the evolution of SCRs is linked to uniform warming, or to changes in circulation patterns, we remove the calendar trend in the Z500 regional average to define SCRs based on detrended data (d‐SCRs). The temporal properties of d‐SCRs appear almost constant whereas their spatial patterns change, indicating that the calendar Z500 regional trend drives the evolutions of SCRs, and that changing spatial patterns in d‐SCRs account for the heterogeneity of this trend. Our study suggests that historical winter conditions will continue to decrease in the future while historical summer conditions continue to increase. However, it also suggests that the spatial and temporal patterns of SCRs would remain similar, relatively to the year‐round Z500 increase.

Wave group focusing in the ocean: estimations using crest velocities and a Gaussian linear model - Paul Platzer; Jean-François Filipot; Philippe Naveau; Pierre Tandeo; Pascal Yiou (Natural Hazards, 2020)

Diagnosing concurrent drivers of weather extremes: application to warm and cold days in North America - Davide Faranda; Gabriele Messori; Pascal Yiou (Climate Dynamics, 2020)

On the low-frequency variability of wintertime Euro-Atlantic planetary wave-breaking - Gabriele Messori; Paolo Davini; M. Carmen Alvarez-Castro; Francesco S. R. Pausata; Pascal Yiou; Rodrigo Caballero (Climate Dynamics, 2019)

Evaluation of the HadGEM3-A simulations in view of detection and attribution of human influence on extreme events in Europe - Robert Vautard; Nikolaos Christidis; Andrew Ciavarella; Carmen Alvarez-Castro; Omar Bellprat; Bo Christiansen; Ioana Colfescu; Tim Cowan; Francisco Doblas-Reyes; Jonathan Eden; Mathias Hauser; Gabriele Hegerl; et al. (Climate Dynamics, 2019)

Behind the veil of extreme event attribution - Aglaé Jézéquel; Vivian Dépoues; Hélène Guillemot; Mélodie Trolliet; Jean-Paul Vanderlinden; Pascal Yiou (Climatic Change, 2018)

Multiple perspectives on the attribution of the extreme European summer of 2012 to climate change - Laura J. Wilcox; Pascal Yiou; Mathias Hauser; Fraser C. Lott; Geert Jan van Oldenborgh; Ioana Colfescu; Buwen Dong; Gabi Hegerl; Len Shaffrey; Rowan Sutton (Climate Dynamics, 2018)

Role of circulation in European heatwaves using flow analogues - Aglaé Jézéquel; Pascal Yiou; Sabine Radanovics (Climate Dynamics, 2018)

Return times of hot and cold days via recurrences and extreme value theory - Davide Faranda; M. Carmen Alvarez-Castro; Pascal Yiou (Climate Dynamics, 2016)

The switching between zonal and blocked mid-latitude atmospheric circulation: a dynamical system perspective - Davide Faranda; Giacomo Masato; Nicholas Moloney; Yuzuru Sato; Francois Daviaud; Bérengère Dubrulle; Pascal Yiou (Climate Dynamics, 2016)

Assessing climate change impacts on European wind energy from ENSEMBLES high-resolution climate projections - Isabelle Tobin; Robert Vautard; Irena Balog; François-Marie Bréon; Sonia Jerez; Paolo Michele Ruti; Françoise Thais; Mathieu Vrac; Pascal Yiou (Climatic Change, 2015)

Characterizing atmospheric circulation signals in Greenland ice cores: insights from a weather regime approach - Pablo Ortega; Didier Swingedouw; Valérie Masson-Delmotte; Camille Risi; Bo Vinther; Pascal Yiou; Robert Vautard; Kei Yoshimura (Climate Dynamics, 2014)

Erratum to: EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

EURO-CORDEX: new high-resolution climate change projections for European impact research - Daniela Jacob; Juliane Petersen; Bastian Eggert; Antoinette Alias; Ole Bøssing Christensen; Laurens M. Bouwer; Alain Braun; Augustin Colette; Michel Déqué; Goran Georgievski; Elena Georgopoulou; Andreas Gobiet; et al. (Regional Environmental Change, 2014)

Trends and variability of seasonal weather regimes - Mathieu Vrac; Pradeebane Vaittinada Ayar; Pascal Yiou (International Journal of Climatology, 2014)
Seasons and seasonality are the main properties of extra‐tropical climate that affect ecosystems and society. For example, agriculture, tourism, energy consumption or ecosystem phenology are primarily dependent on seasonality and on the magnitude of the meteorological events associated within each season. Changes in the seasonality of variables like surface temperature during the last decades have been widely investigated but seasonal changes of the weather have received less quantification. This paper redefines the concept of seasonality based on the extra‐tropical atmospheric circulation, and on the notion that it can drive the evolution of temperature. We find that summer‐like atmospheric conditions have appeared earlier and ended later since 1948. Conversely, the period with winter patterns has reduced over that period. The temperatures associated with weather patterns allow to identify the sources of temperature trends.

The simulation of European heat waves from an ensemble of regional climate models within the EURO-CORDEX project - Robert Vautard; Andreas Gobiet; Daniela Jacob; Michal Belda; Augustin Colette; Michel Déqué; Jesús Fernández; Markel García-Díez; Klaus Goergen; Ivan Güttler; Tomáš Halenka; Theodore Karacostas; et al. (Climate Dynamics, 2013)

Ensemble reconstruction of the atmospheric column from surface pressure using analogues - Pascal Yiou; Tamara Salameh; Philippe Drobinski; Laurent Menut; Robert Vautard; Mathieu Vrac (Climate Dynamics, 2013)

Summer temperatures in Europe and land heat fluxes in observation-based data and regional climate model simulations - Annemiek I. Stegehuis; Robert Vautard; Philippe Ciais; Adriaan J. Teuling; Martin Jung; Pascal Yiou (Climate Dynamics, 2013)

North-Atlantic dynamics and European temperature extremes in the IPSL model: sensitivity to atmospheric resolution - Julien Cattiaux; Benjamin Quesada; Ara Arakélian; Francis Codron; Robert Vautard; Pascal Yiou (Climate Dynamics, 2013)

Dynamics of future seasonal temperature trends and extremes in Europe: a multi-model analysis from CMIP3 - Julien Cattiaux; Pascal Yiou; Robert Vautard (Climate Dynamics, 2012)

North-Atlantic SST amplified recent wintertime European land temperature extremes and trends - Julien Cattiaux; Robert Vautard; Pascal Yiou (Climate Dynamics, 2011)

Simulation of regional climate change under the IPCC A2 scenario in southeast China - Weilin Chen; Zhihong Jiang; Laurent Li; Pascal Yiou (Climate Dynamics, 2011)